Murder, she edited - Dunnett, Kaitlyn (Dunnett, Kaitlyn. Deadly edits mystery., 2021)
"As the hesitant new owner of a rundown property outside of sleepy Lenape Hollow, New York, freelance editor Mikki Lincoln must get her facts straight about an old murder on the premises -- before the killer returns to meet the next deadline! When Mikki inherits a nearby farm from a woman she hasn't seen in two decades, the unexpected arrangement comes with a big catch: forgotten diaries hidden in the neglected house must be recovered, edited, and published across the internet within one month. The lonely locale is like an untouched time capsule from the 1950s, and it was left behind for good reason. While searching for the mysterious memoirs and clues about the former owners, Mikki discovers that the once peaceful place was punctuated by an unsolved homicide and other rumored crimes. Worse, suspicious activity in the creepy, dilapidated barn suggests it really hasn't been abandoned at all... In a remote farmhouse with only her observant calico cat, Calpurnia, keeping her company, Mikki must swiftly crack an eerie cold case from the past and stop a clever culprit from leaving red markups on anything other than pages of revised copy..." --